PERSEPSI SISWA KELAS 5 MI DARUL ULUM 2 TERHADAP PENGGUNAAN GADGET BERLEBIHAN MELALUI LAYANAN BK : Pendahuluan, Metode Penelitian, dan Hasil Pembahasan - Eva Noor Safitri; Diki Candra Febriansyah; Anita Susi Fatmasari; Mahfudhoh Angelita Sari; Davina Natania Himawan; Ade Sucipto (Jurnal Prasasti Ilmu, 2026)
Gadgets are not only used as a means of communication and entertainment, but are also used in learning activities through digital media such as educational videos. This study was conducted with the aim of describing the perceptions of fifth-grade students at MI Terpadu Darul Ulum 02 regarding excessive gadget use through classical guidance and counseling services assisted by educational videos. A qualitative approach with descriptive research type was used in this study. Research data were obtained through observation and interviews. The research subjects consisted of fifth-grade students who participated in classical guidance and counseling services at school. The results showed that students' understanding of the impact of excessive gadget use increased after being provided with classical guidance and counseling services assisted by educational videos. The negative impacts of gadget use were understood by students as causing decreased learning concentration, reduced social interaction, eye health problems, and the emergence of excessive gadget playing habits. In addition, the use of educational video media was considered able to increase student activity and enthusiasm during the service activities